Analysis the Effect of Short Term Debt on Earnings Management in Companies Listed on Indonesian Stock Exchange - Sukiantono Tang; Lina Wati (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
The purpose of this research is to examine the impact of short term debt on earnings management. The independent variable include is short term debt. The dependent variable is earnings management which is measured by (Dechow & Dichev, 2002) modified by (McNichols, 2002) model. This research used purposive sampling to non-financial companies which are listed in Indonesia Stock Exchange from 2014-2018. The data was analyzed by data panel regression. The result of this research indicates that short term debt has a significant positive effect on earnings management in companies with high short tern debt values and significant negative effect in companies with low short term debt values.